2020
DOI: 10.1016/j.arcmed.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Defective Anti-oxidant System: An Aggravating Factor for COVID-19 Patients Outcome?

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Nevertheless, significant alterations in vitamin C, GSH and selenium concentrations, all molecules playing a key role in the immunity, raise questions in the particular framework of the COVID-19 pathogenesis. Associated to increased lipid peroxidation, these observations should therefore create opportunities to explore potential approaches for prevention or treatment by antioxidants, as observed in COVID-19 patients [ 76 , 77 , 78 , 79 , 80 ]. As recently suggested for vitamin C and glutathione [ 33 , 47 , 81 ], monitoring of OSS should be implemented in COVID-19 critically ill patients, including vitamin C, GSH in association with PSH, and, finally, ROOH in association with the Cu/Zn ratio and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, significant alterations in vitamin C, GSH and selenium concentrations, all molecules playing a key role in the immunity, raise questions in the particular framework of the COVID-19 pathogenesis. Associated to increased lipid peroxidation, these observations should therefore create opportunities to explore potential approaches for prevention or treatment by antioxidants, as observed in COVID-19 patients [ 76 , 77 , 78 , 79 , 80 ]. As recently suggested for vitamin C and glutathione [ 33 , 47 , 81 ], monitoring of OSS should be implemented in COVID-19 critically ill patients, including vitamin C, GSH in association with PSH, and, finally, ROOH in association with the Cu/Zn ratio and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to study whether an intrinsically defective anti-oxidant system, such as G6PD deficiency or other causes, is activated in response to COVID-19 infection [ 109 , 110 ]. Moreover, the use of anti-oxidant therapy may help in inhibiting COVID-19 pathology [ 111 , 112 , 113 ].…”
Section: Oxidative Stress and Apoptosis In Covid-19mentioning
confidence: 99%
“…Recently, different researchers have suggested that oxidative stress in patients with COVID-19 could contribute to cytokine storm and coagulopathy 8 , 9 , 10 , 11 , 12 , 13 , 14 . In vitro studies have found that SARS-CoV-1 infection increases the production of ROS in human promonocyte cells 26 and in various mammalian cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Since COVID-19 was declared as a pandemic disease, a large number of investigations have been carried out to better understand its epidemiology, mechanisms, clinical evolution, and management. Recently, several researchers have suggested the potential role of oxidative stress on COVID-19 and it has been proposed that oxidative stress in patients with COVID-19 could contribute in the cytokine storm and coagulopathy; in addition, the use of antioxidants agents has been suggested to reduce oxidative stress 8 , 9 , 10 , 11 , 12 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%